Emission enhancement and high sensitivity of a π-conjugated dye towards pressure: the synergistic effect of supramolecular interactions and H-aggregation. Issue 32 (3rd April 2019) - Sun, Zhanghua; Zang, Qiguang; Luo, Qing; Lv, Chunyan; Cao, Feng; Song, Qingbao; Zhao, Ruiyang; Zhang, Yujian; Wong, Wai-Yeung
Abstract : We prepared a HLCT-type dye with high PL efficiency in solid solutions. In the crystalline state, the H-aggregated dye with weak supramolecular interactions showed enhanced emission under low pressures (5 MPa). Abstract : Piezoresponsive fluorescent (PRF) materials are highly promising for applications in deformation, flaw detection and haptic sensing. However, traditional PRF materials generally suffer from low sensitivity and fluorescence quenching processes. This study involved the preparation of H-aggregated dyes with weak supramolecular interactions, which showed enhanced emission under a low pressure.